2011
DOI: 10.1007/s00018-011-0726-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of the precursor structure in the biogenesis of microRNA

Abstract: The human genome contains more than 1,000 microRNA (miRNA) genes, which are transcribed mainly by RNA polymerase II. The canonical pathway of miRNA biogenesis includes the nuclear processing of primary transcripts (pri-miRNAs) by the ribonuclease Drosha and further cytoplasmic processing of pre-miRNAs by the ribonuclease Dicer. This review discusses the issue of miRNA end heterogeneity generated primarily by Drosha and Dicer cleavage and focuses on the structural aspects of the Dicer step of miRNA biogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 147 publications
(201 reference statements)
3
100
0
Order By: Relevance
“…miRNAs are known to play their roles, if not exclusively, in the cytoplasm. 29 However, MIAT was found to be a nuclear-localized lncRNA, raising the possibility that miR-150-5p targets MIAT in the nucleus. RNA-fluorescent in situ hybridization experiment revealed that miR-150-5p was expressed in the cytoplasm and nucleus of RF/6A cells ( Figure 5C), which was consistent with previous studies.…”
Section: Lncrna-miat Functions As Mir-150-5p Sponge In Endothelial Cellmentioning
confidence: 99%
“…miRNAs are known to play their roles, if not exclusively, in the cytoplasm. 29 However, MIAT was found to be a nuclear-localized lncRNA, raising the possibility that miR-150-5p targets MIAT in the nucleus. RNA-fluorescent in situ hybridization experiment revealed that miR-150-5p was expressed in the cytoplasm and nucleus of RF/6A cells ( Figure 5C), which was consistent with previous studies.…”
Section: Lncrna-miat Functions As Mir-150-5p Sponge In Endothelial Cellmentioning
confidence: 99%
“…The signal for Hs_154 appears as a doublet, indicating a 21-to 22-nucleotide (nt) form, as well as slightly larger form. This may be due to heterogeneity at the miRNA 3= ends, a phenomenon frequently observed in miRNA biogenesis (30,47,54).…”
Section: Wnv Infection Alters the Expression Level Of Multiple Cellulmentioning
confidence: 99%
“…Sequences encoding miRNAs are found around the genome as separate transcriptional units, although a minority of these sequences are located within the introns of coding genes (generally as clustered miRNAs; Kapinas & Delany 2011). miRNAs are first transcribed as long primary units called pri-miRNAs, which contain characteristic secondary loop structures (Starega-Roslan et al 2011). Various miRNAs can be co-transcribed in a single pri-miRNA, possibly inducing additional effects on a single pathway or gene or allowing crosstalk between different pathways (He et al 2010).…”
Section: Introductionmentioning
confidence: 99%